Kemampuan Berpikir Kreatif Siswa dalam Mem-posing Masalah menggunakan Pendekatan Pendidikan Matematika Realistik Indonesia - Elisa Anggraini; Zulkardi Zulkardi (Jurnal Elemen, 2020)
This research aims to obtain a picture of how students' creative thinking abilities in proposing problems using Pendidikan Matematika Realistik Indonesia (PMRI) approach on the material of number patterns. This research uses descriptive research with the research subject is students of class VIII at SMP Negeri 15 Palembang. The learning process in the class was carried out by the PMRI approach. Data collection techniques used in this study were tests, observations, and interviews. Observations were made to see the indicators that emerge when the learning process was carried out. Tests were conducted to determine students' creative thinking abilities when working on and proposing problems. At the same time, interviews were used to confirm answers to student test results. The results are divided into five levels, namely level 0 to level 4, with different characteristics at each level. In this research, there are four students with very creative abilities, 18 students with creative abilities, two students with less creative abilities, and two students with non-creative abilities. The difference in each level is based on fluency, flexibility, and novelty in posing problems.